1987
DOI: 10.1111/j.1432-1033.1987.tb11156.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the redox‐linked proton ejection in beef‐heart cytochrome c oxidase reconstituted in liposomes

Abstract: In this paper a study is presented of the characteristics of redox‐linked proton ejection exhibited by isolated beef‐heart cytochrome c oxidase incorporated in asolectin vesicles. The enzyme was 90% oriented ‘right‐side out’ as in the mitochondrial membrane. The effects on the H+/e− stoichiometry of the modalities of activation of electron flow, the pH of the medium and its ionic composition were investigated. The results obtained show that, whilst ferrocytochrome c pulses of the aerobic oxidase vesicles at ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 62 publications
1
24
0
Order By: Relevance
“…The results of the investigations, based on measurement of the rates of electron £ow and proton ejection at level £ow, showed that the H /e 3 ratio of proton pumping by the oxidase varies, both in intact mitochondria and in the isolated-reconstituted oxidase, from around zero, at extremes of low and high rates, to about one at intermediate rates (see also [14]). It was also found that the H /e 3 ratios for proton ejection driven by ferrocytochrome c oxidation in COV increase with pH, up to about one at a pH around 8 and then decline at higher pHs [21]. When compared with the pH dependence of redox Bohr effects in the soluble oxidase, the pH dependence of the H /e 3 ratio for proton pumping is similar to that observed for the H /e 3 ratio of the Bohr e¡ect linked to oxido-reduction of heme a (Fig.…”
Section: Features Of the Proton Pump In Cytochrome C Oxidasementioning
confidence: 96%
See 1 more Smart Citation
“…The results of the investigations, based on measurement of the rates of electron £ow and proton ejection at level £ow, showed that the H /e 3 ratio of proton pumping by the oxidase varies, both in intact mitochondria and in the isolated-reconstituted oxidase, from around zero, at extremes of low and high rates, to about one at intermediate rates (see also [14]). It was also found that the H /e 3 ratios for proton ejection driven by ferrocytochrome c oxidation in COV increase with pH, up to about one at a pH around 8 and then decline at higher pHs [21]. When compared with the pH dependence of redox Bohr effects in the soluble oxidase, the pH dependence of the H /e 3 ratio for proton pumping is similar to that observed for the H /e 3 ratio of the Bohr e¡ect linked to oxido-reduction of heme a (Fig.…”
Section: Features Of the Proton Pump In Cytochrome C Oxidasementioning
confidence: 96%
“…The observed non-linearity of the steady-state relationship between respiratory rate and vp is taken by some authors as evidence of slip in proton pumps [19], by others as due to non-ohmic increases of membrane proton conductance at high vp (leak) [20]. Papa et al have carried out an extensive study of the in£u-ence of kinetic and thermodynamic factors on the H /e 3 stoichiometry of cytochrome c oxidase in mitochondria and in the isolated-reconstituted state (COV) [17,18,21]. The results of the investigations, based on measurement of the rates of electron £ow and proton ejection at level £ow, showed that the H /e 3 ratio of proton pumping by the oxidase varies, both in intact mitochondria and in the isolated-reconstituted oxidase, from around zero, at extremes of low and high rates, to about one at intermediate rates (see also [14]).…”
Section: Features Of the Proton Pump In Cytochrome C Oxidasementioning
confidence: 99%
“…The measured q+/2e stoichiometry of cytochrome oxidase at low Ay approaches the most widely accepted value of 4 at level flow [22][23][24]26, 271. As we have indicated [l], this method may slightly underestimate the stoichiometry; therefore a reasonable interpretation of the observed drop in the q+/2e stoichiometry of cytochrome oxidase in these experiments is that it changes from 4 at low values of Ap to 2 at high values of Ap, although other absolute values of 4+/2e are not rigorously excluded by these results.…”
Section: Discussionmentioning
confidence: 99%
“…that (for example) values considerably less than unity have been observed (3,(13)(14)(15), depending on the total number of turnovers, the absolute turnover rate, and the initial state of the enzyme, either pulsed or resting (for definition, see refs. 16 and 17).…”
mentioning
confidence: 99%